Identification of Candida species in faeces of children with Autism Spectrum Disorder (ASD) carbohydrate and noncarbohydrates diets - Yuni Retnaningtyas; Dewi Dianasari; Luna Ivanka Dwi Elavia; Ulfatul Munawaroh (Department of Nutrition at the Health Polytechnic of Aceh, Ministry of Health, 2022)
Increased colonization of Candida, especially C. albicans can occur in children with ASD and cause the severity of symptoms. One of the triggers for increased colonization in ASD children is the consumption of carbohydrates. This study aimed to identify Candida species in the faeces of ASD children who diet and nondiet carbohydrates from schools with special needs in Jember, East Java. The research design is a true experimental laboratory. The sample consisted of 26 ASD children and 13 healthy children as controls, with different subjects calculated using the Krejcie and Morgan formula. The test samples were identified for fungi by examining germ tube morphology, chlamydospores, and Candida species and compared with controls. The results showed differences in Candida species in the two test groups. Species C. albicans, C. dubliniensis, and C. tropicalis were found in almost all the faeces of ASD children with noncarbohydrates diet. The species C. parapsilosis, and C. albicans were found in a small proportion of the faeces of ASD children's carbohydrate diet. In contrast, the species found in the control group were C. albicans, C. dubliniensis, C. parapsilosis, and C. glabrata. In conclusion, carbohydrate consumption can affect the Candida species in the faeces of children with ASD.